2008
DOI: 10.1016/j.neuint.2007.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Over-expressed human divalent metal transporter 1 is involved in iron accumulation in MES23.5 cells

Abstract: Elevated iron accumulation has been reported in brain regions in some neurodegenerative disorders. However, the mechanism for this is largely unknown. Divalent metal transporter 1 (DMT1) is an important divalent cation transporter. The aim of the present study is to construct recombinant adenovirus encoding human DMT1 with iron responsive element (DMT1 + IRE) and infect MES23.5 dopaminergic cells in order to investigate the relationship between increased DMT1 + IRE expression and iron accumulation. The human D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Similar to previous studies, divalent metal transporter-1 was observed to be up-regulated by MPTP (59) and this increase was sustained even in the presence of DHB (data not shown). Recent studies suggest that overexpression of divalent metal transporter-1 alone is associated with intracellular iron accumulation (60) and MPTP-induced apoptosis (61), however, these detrimental effects appear to be overridden by other HIF-related events in our system.…”
Section: Discussionmentioning
confidence: 92%
“…Similar to previous studies, divalent metal transporter-1 was observed to be up-regulated by MPTP (59) and this increase was sustained even in the presence of DHB (data not shown). Recent studies suggest that overexpression of divalent metal transporter-1 alone is associated with intracellular iron accumulation (60) and MPTP-induced apoptosis (61), however, these detrimental effects appear to be overridden by other HIF-related events in our system.…”
Section: Discussionmentioning
confidence: 92%
“…Cell Culture MES23.5 cells were offered by Dr. Wei-dong Le (Baylor College of Medicine, TX, USA) and cultured as previously described (Xu et al 2008;Zhang et al 2008). For experiments, cells were seeded at a density of 1×10 5 per square centimeter in the plastic flasks or plates.…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear morphological changes were detected using the method described before (Xu et al 2008;Zhang et al 2008). MES23.5 cells were seeded on sterile cover glasses placed in a six-well plate at a density of 1.0×10 4 cells per square centimeter.…”
Section: Hoechst 33258 Stainingmentioning
confidence: 99%
“…Nuclear morphology was detected using the method previously described from our laboratory (Xu et al, 2008;Zhang et al, 2008). MES23.5 cells were seeded on glass coverslips in 24-well plates and incubated with zinc as described above for 1, 2, 4, 8, 16, and 24 hr.…”
Section: Hoechst 33258 Stainingmentioning
confidence: 99%